Equivalence of error-correcting quaternary [6, 3] self-dual codes. Issue 3 (19th May 2017) - Elora, Farzana Karim; Dey, Partha Pratim
Abstract: In an earlier paper [1], we were able to classify all 1-error correcting quaternary [5, 2] codes into 4 disjoint equivalence classes. Pursuing the same ideas, in this paper, we investigate the 1–error correcting self-dual [6, 3] codes over GF (4).We are able to show that these codes are all mutually permutation equivalent.